Bioinformatic analysis of dihydrofolate reductase predicted in the genome sequence of Lactobacillus pentosus KCA1 (Nigerian Journal of Physiological Sciences, 2021)
Summary: Physiologic studies of Lactobacillus species show that some species cannot synthesize folate de novo, which is required for growth. Folate plays a critical role in regulating the amount of tetrahydrofolate in the cell that is utilized for DNA replication, and proliferation of the erythropoietic system. We recently sequenced the genome of Lactobacillus pentosus KCA1, isolated from a Nigerian subject. The genome has open reading frames coding for the complete genes required for folate biosynthesis. Our previous study shows that rats fed with L. pentosus KCA1 led to enhancement of haematological parameters. Bioinformatic tool such as ClustalW algorithm was used to analyze dihydrofolate reductase (folA/dfrA) encoded in the genome sequence of L. pentosus KCA1 for comparative multiple sequence alignments. I-TASSER was used to predict the 3-D model structure of the protein and potential active binding site residues. Result show that two unique amino acid substitutions were found in KCA1_1610 sequence at position 85 with alanine (A-Ala85), while other strains have aspartic acid (D-Asp) for other L. pentosus and threonine (T-Thr) for L. plantarum strains at the same position. The result suggests that dihydrofolate reductase can be used as a distinguishing marker between L. pentosus KCA1 and other pentosus including L. plantarum strains. The secondary structure prediction with I-TASSER revealed 5 alpha helices and 8 beta-strands. Twelve binding site residues were predicted in KCA1_1610 relative to the template protein 2zzaA in protein database (PDB). The predicted structure of KCA1_1610 dihydrofolate reductase can serve as a new template as an addition to structural genomics and generation of models for use in drug screening and physiological function inference.